2017
DOI: 10.1161/jaha.117.006472
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Modulates Arrhythmia Substrates During Different Phases of Resuscitation From Ischemic Cardiac Arrest

Abstract: BackgroundWe designed an innovative porcine model of ischemia‐induced arrest to determine dynamic arrhythmia substrates during focal infarct, global ischemia from ventricular tachycardia or fibrillation (VT/VF) and then reperfusion to determine the effect of therapeutic hypothermia (TH) on dynamic arrhythmia substrates and resuscitation outcomes.Methods and ResultsAnesthetized adult pigs underwent thoracotomy and regional plunge electrode placement in the left ventricle. Subjects were then maintained at either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Targeted temperature management (TTM; therapeutic hypothermia) may reduce damage to the central nervous system as tracked by biomarkers(34), and also reduce metabolic demands or arrhythmias(35). Nevertheless, the role of TTM is under discussion(36) as it has been linked to events such as coronary (stent) thrombosis(37).…”
Section: Respondmentioning
confidence: 99%
“…Targeted temperature management (TTM; therapeutic hypothermia) may reduce damage to the central nervous system as tracked by biomarkers(34), and also reduce metabolic demands or arrhythmias(35). Nevertheless, the role of TTM is under discussion(36) as it has been linked to events such as coronary (stent) thrombosis(37).…”
Section: Respondmentioning
confidence: 99%
“…These phases have distinct electrophysiological properties that are not accounted for by current ACLS protocols, and the interplay of arrhythmia substrates and susceptibilities during each phase is unknown. All these phases can be incorporated into a large animal porcine model (22). In vivo porcine models have provided important results on resuscitation approaches and outcomes, although mechanistic information on arrhythmia formation and maintenance is less well-understood (49, 50, 53, 54).…”
Section: Models Of Specific Arrhythmogenic Diseasementioning
confidence: 99%
“…We recently reported that in a porcine translational model of ischemia-induced SCA that arrhythmia substrates were in fact dynamic during different phases of resuscitation that they were modified by therapeutic hypothermia. In addition, cardiac alternans was an important mechanism of recurrent VF during resuscitation (22). Regarding species specific models of cardiopulmonary resuscitation, the advantages of transmural and regional ion currents, more human like conduction system and lower susceptibility to VF in dog vs. pig is a consideration when evaluating outcomes or therapies (11, 14).…”
Section: Models Of Specific Arrhythmogenic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, such studies have shed considerable light on how therapeutic hypothermia affects various aspects of the organ response to CA, including the heart, brain, and immune system. 3 , 4 , 5 , 6 , 7 However, pig and rat models have critical limitations, which include difficulties in genetically modulating specific genes or pathways to perform detailed mechanistic studies. Consequently, mouse models have been increasingly used in experimental CA research.…”
mentioning
confidence: 99%